2012
DOI: 10.1111/j.1467-9906.2012.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Investors: The Missing Piece in the Foreclosure Racial Gap Debate

Abstract: Foreclosures have become one of the most important problems facing cities and the U.S. economy. However, not all communities are affected equally. Our goal is to better understand factors that affect variation in neighborhood foreclosures in a typical, mid‐sized U.S. city—Louisville, Kentucky. While previous findings indicate that a key explanatory variable leading to rising neighborhood foreclosures is the proportion of racial minorities, our analysis finds that in a fully specified model, race does not predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Yet the remaining sample statistics reveal other important differences between black and white borrowers that might plausibly account for racial disparities in lending terms and foreclosure rates. For example, blacks evince a greater likelihood of borrowing at the housing bubble's peak in 2006 as well as lower incomes, credit scores, and rates of neighborhood educational attainment, all factors that prior studies have shown to undermine loan performance and raise the odds of default and foreclosure (e.g., Anacker and Carr 2011; Chan et al 2013; Ding et al 2011; Gilderbloom et al 2012; Pennington-Cross and Ho 2010). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the remaining sample statistics reveal other important differences between black and white borrowers that might plausibly account for racial disparities in lending terms and foreclosure rates. For example, blacks evince a greater likelihood of borrowing at the housing bubble's peak in 2006 as well as lower incomes, credit scores, and rates of neighborhood educational attainment, all factors that prior studies have shown to undermine loan performance and raise the odds of default and foreclosure (e.g., Anacker and Carr 2011; Chan et al 2013; Ding et al 2011; Gilderbloom et al 2012; Pennington-Cross and Ho 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Whereas 79% of whites lived in tracts that were less than 50% black, 81% of blacks lived in tracts that were at least 50% black. Although 21% of white borrowers appeared to live in black neighborhoods, close inspection of these cases revealed many to be investors who likely lived elsewhere (see Gilderbloom et al 2012). While rising gentrification partly fueled by the subprime mortgage boom may have integrated black and white households in resurgent cities such as Washington, DC, black-white segregation may have been exacerbated in cities such as Baltimore (Bond and Williams 2007; Fischer 2013; Friedman et al 2012; Friedman, Tsao, and Chen 2013; Hyra and Rugh forthcoming; Lichtenstein and Weber 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that this effect is a fluke created by the interactions of the variables in the model or that it is capturing the effect of an omitted independent variable. Another possible explanation might be that this variable is in part capturing the presence of investor foreclosures-a driving force behind higher urban foreclosure rates (Gilderbloom, Ambrosius, Squires, Hanka, & Kenitzer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…however, its moderate size and mid-western location make Louisville representative of the average US city (Gilderbloom, Ambrosius, Squires, Hanka, & Kenitzer, 2012;Savitch & Vogel, 2004).…”
mentioning
confidence: 99%